Simple and Sensitive Colorimetric Detection of Dopamine Based on Assembly of Cyclodextrin‐Modified Au Nanoparticles. Issue 18 (22nd March 2016) - Wen, Dan; Liu, Wei; Herrmann, Anne‐Kristin; Haubold, Danny; Holzschuh, Matthias; Simon, Frank; Eychmüller, Alexander
Abstract : A controlled assembly of natural beta‐cyclodextrin modified Au NPs mediated by dopamine is demonstrated. Furthermore, a simple and sensitive colorimetric detection for dopamine is established by the concentration‐dependent assembly.